2014
DOI: 10.4028/www.scientific.net/amr.911.55
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Porous Alumina Layer and Cerium Sealing of Al7xxx/SiC Composite for Structural Lightweight Alloy Corrosion Resistant Application

Abstract: AMC (Aluminum Matrix Composite) as a main material for automotive and aircraft applications has the keyadvantage that islighter thanaluminumalloys. So, it can be ascertained that fuel comsumption forthoseapplicationswill be reduced. However, AMC materials are generally suceptible to galvanic corrosion due to galvanic reaction between aluminum matrix and reinforcement, and the formation of microstructure at matrix/reinforcement interface as well. Anodizing is the most effective surface modification method in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Temperature plays an important role during the anodizing process and significantly affects the morphology of porous AAO (Sulka & Parkoła, 2007;Theohari & Kontogeorgou, 2013). Our previous study showed that an appropriate anodizing temperature produced a porous morphology with good adhesion properties for further coating (Rizkia et al, 2014;Rizkia et al, 2015). Higher anodizing temperature resulted in higher current density and the chemical dissolution of the oxide surface, resulting in porous AAO with wider pores and thinner pore walls (Sulka & Parkoła, 2007;Zahariev et al 2008;Aerts et al, 2009;Aerts et al, 2010Zaraska et al, 2013Kao & Chang, 2014).…”
mentioning
confidence: 99%
“…Temperature plays an important role during the anodizing process and significantly affects the morphology of porous AAO (Sulka & Parkoła, 2007;Theohari & Kontogeorgou, 2013). Our previous study showed that an appropriate anodizing temperature produced a porous morphology with good adhesion properties for further coating (Rizkia et al, 2014;Rizkia et al, 2015). Higher anodizing temperature resulted in higher current density and the chemical dissolution of the oxide surface, resulting in porous AAO with wider pores and thinner pore walls (Sulka & Parkoła, 2007;Zahariev et al 2008;Aerts et al, 2009;Aerts et al, 2010Zaraska et al, 2013Kao & Chang, 2014).…”
mentioning
confidence: 99%